Tenth-Graders’ Perceptions towards the Use of Google Classroom for Writing Class - Maidatul Khasanah; Sri Wahyuni (Jurnal Pedagogy, 2023)
The world of education today is closely related to the development of scientific and technological advances. Google Classroom is a useful platform to help the online learning process, especially in learning English. This study aims to determine students’ perceptions of using Google Classroom as a learning medium in writing class. This study used a quantitative descriptive research design. The research subjects were all tenth-grade students in one of the senior high schools in Wates, Central Java, Indonesia. The population of the study consisted of 385 students, but the researchers took a sample of 30% of the total from all tenth-grade students. The researcher used a questionnaire and interview as a data collection method. The researcher analyzed the data statistically by calculating the percentage of students’ answers using Microsoft Excel. This study finds that students have a positive perception of using Google Classroom in writing class. Moreover, it can be concluded that Google Classroom has a good influence in supporting learning for English Foreign Language students.